Keuntungan Algoritma Bezier, B-Spline di Dunia Industri - Djunaidy Santoso; Haryono Soeparno; Ayuliana Ayuliana (Bina Nusantara University, 2013)
Graphic Computers are widely used in various fields, especially in industries, companies, banks and hospitals. At hospital, computer graphics with leading edge techniques support images related to patient's needs. Graphic computer can also be used for shipbuilding and automotive design, as well as decision-makers in an institution, using pictures or images that can be analyzed to produce good forms which the accuracy is still investigated (CAD and CAM). The purpose of research is linking algorithms by creating the right picture or image to a form required by decision makers to associate algorithms Hermite, Bezier, B-Spline in harmonious function of each, so that the curves, images or images are produced better, and can be used in the field of engineering drawings. This research produces an image/ shape/ image which are suitable for designers’ need.